Length-weight relationship of the Indian horseshoe crab Tachypleus gigas (Muller) - Chatterjee, Anil; Mishra, J K; Vijayakumar, R; Parulekar, A H (Indian Journal of Fisheries, 2011)
The length-weight relationship, besides providing a mathematical relationship, also yields information on the general well-being, variation in growth with sex, size at first maturity, gonad development and breeding season.